Volatile and Non-Volatile Organic Compounds Stimulate Oviposition by Aphidophagous Predators - Eric W. Riddick (Insects, 2020)
Introduction: Evidence that volatile organic compounds (VOCs) and non-VOCs stimulate oviposition by aphidophagous predators is scattered throughout the literature. The objectives of this review are to (1) compile records indicating that VOCs and non-VOCs are responsible for oviposition stimulation, (2) calculate an egg production ratio (EPR) for stimulated predators, and (3) determine if EPR is correlated with vapor pressure and molecular weight of active compounds. Methods: The USDA (United States Department of Agriculture), National Agricultural Library, online digital catalog system was used to retrieve abstracts, then the full text of manuscripts on oviposition stimulants for predators. Oviposition-stimulating VOCs and non-VOCS were tabulated with molecular weights and vapor pressure estimates. EPRs were calculated for stimulated coccinellids, syrphids, and chrysopids. Results: Both VOCs and non-VOCs stimulated oviposition behavior by coccinellids and syrphids, but not chrysopids. EPR was greatest for syrphids. Two VOCs, (E)-β-farnesene and 3-methyl-2-butenal, stimulated very high EPR values by the syrphid Episyrphus balteatus. Regardless of predator taxa, EPR was negatively and positively correlated with molecular weight and vapor pressure, respectively. Conclusions: Syrphids (rather than coccinellids or chrysopids) produce more eggs in response to VOCs. Organic compounds with low-to-moderate molecular weights and moderate-to-high vapor pressures might be most effective oviposition stimulants for aphidophagous predators.